Occurrence of Disease and Syndrome Eponyms in the Titles of Medical Literature - Ghosh, Jata S. (Methods of Information in Medicine, 1975)
No quantitative data on the use of eponyms in medicine are available. This paper attempts to quantify the frequency of occurrence of 91 personalized disease and syndrome eponyms (DSE) in the titles of medical documents. By employing the subject heading-title word correlation technique of Montgomeryand Swansonit was found that 72.2 percent of the 2,435 papers listed in the 1973 Index Medicushad at least one of these 91 candidate DSEs in their titles; another 195 (8.0 percent) titles had the corresponding descriptive or non-eponymic synonyms, and the remaining 480 (19.8 percent) titles did not have either of these two matching elements. Thus, the ratio of occurrence of the personalized DSEs to their descriptive names in the titles of the medical literature examined appeared to be 9:1. It was further noted that, while about 80 percent of the pertinent literature could be retrieved on the basis of a title search with DSEs and their descriptive synonyms, about 20 percent of the relevant documents will be missed.
Keywords: Medizinische Eponyme; Stichwort-Recherchen; Dokumenten-Auswahl; Information Retrieval